2016
DOI: 10.1038/srep24187
|View full text |Cite
|
Sign up to set email alerts
|

Large-deformation and high-strength amorphous porous carbon nanospheres

Abstract: Carbon is one of the most important materials extensively used in industry and our daily life. Crystalline carbon materials such as carbon nanotubes and graphene possess ultrahigh strength and toughness. In contrast, amorphous carbon is known to be very brittle and can sustain little compressive deformation. Inspired by biological shells and honeycomb-like cellular structures in nature, we introduce a class of hybrid structural designs and demonstrate that amorphous porous carbon nanospheres with a thin outer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 37 publications
2
27
0
1
Order By: Relevance
“…In 1959 Ergun and Tiensuu [57] gave another interpretation of the XRD patterns of non-graphitising carbons. They showed that clusters of tetrahedrally-bonded carbon atoms give rise to diffraction bands in approximately the same angular region as the two-dimensional (10) and (11) reflections of graphene layers, that is at values s = 2sinθ/λ (θ is the scattering angle and λ is the wavelength) of about 0.5 Å −1 and 0.85 Å −1 , as can be seen in Figure 13. Therefore, they argued that from the broad, diffuse diffraction peaks of non-graphitising carbons it is very difficult to completely rule out the presence of diamond-like structures.…”
Section: Glass-like Carbon and Other Pyrolysed Non-graphitising Carbonsmentioning
confidence: 90%
See 1 more Smart Citation
“…In 1959 Ergun and Tiensuu [57] gave another interpretation of the XRD patterns of non-graphitising carbons. They showed that clusters of tetrahedrally-bonded carbon atoms give rise to diffraction bands in approximately the same angular region as the two-dimensional (10) and (11) reflections of graphene layers, that is at values s = 2sinθ/λ (θ is the scattering angle and λ is the wavelength) of about 0.5 Å −1 and 0.85 Å −1 , as can be seen in Figure 13. Therefore, they argued that from the broad, diffuse diffraction peaks of non-graphitising carbons it is very difficult to completely rule out the presence of diamond-like structures.…”
Section: Glass-like Carbon and Other Pyrolysed Non-graphitising Carbonsmentioning
confidence: 90%
“…Nowadays, TEM is still a driving force for the structural studies of carbon materials and the development of their technology. It is especially worth mentioning recent advances in in situ and real-time TEM experiments which allow observing and recording the behaviour of carbons in different conditions, such as heating, stress, pressure, and electron beam [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanical behavior of HCSs would provide important implications of the fundamental mechanisms on how to improve the structural durability of the devices and systems for engineering applications. 19 To date, there has been little reported work in this field. 20 Herein, we report the preparation of BHCSs based on the compression of HCSs with structural robustness.…”
mentioning
confidence: 99%
“…Например, микропористые структуры используются для удаления из биологических жидкостей продуктов небольшой молекулярной массы. В настоящее время известны разнообразные пористые углеродные микро-и наноструктуры [1][2][3][4][5][6]. Плотность таких структур колеб-лется от 0.26 до 2.2 g/сm 3 [2].…”
Section: Introductionunclassified